Optimalisasi Pemberdayaan Kelompok Wanita Tani Mawar Bodas di Kelurahan Kahuripan Kecamatan Tawang Kota Tasikmalaya - Aulya S Rahmawati; Siti Komariah; Mirna Nur Alia Abdullah (Ideas Publishing, 2023)
This research began with the discrepancy between Tasikmalaya City government regulations and farmers' actual experiences with Women Farmer Groups, in terms of fostering and facilitating farmer institutional empowerment. The goal of this study was to find out how much the Women Farmer Group's skills and welfare were improved by farming community empowerment. The study employs a qualitative approach. Observation, interviews, and documentation are the methods used in this study to collect data. The study's findings indicate that the empowerment measures for the Mawar Bodas Women Farmers Group (KWT) have not been fully implemented.